The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1093/gerona/53a.6.m441
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Genetic Factors for Longevity: A Comparison of Identical and Fraternal Twins in the Swedish Twin Registry

Abstract: Over the total age range examined, a maximum of around one third of the variance in longevity is attributable to genetic factors, and almost all of the remaining variance is due to nonshared, individual specific environmental factors. The evidence that genetic factors play a minor role depending upon age at death merits further examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
2
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(130 citation statements)
references
References 13 publications
3
122
2
1
Order By: Relevance
“…It is worth noting that the above evidence for a substantial and significant genetic effect on the likelihood of reaching exceptionally old age is not inconsistent with several twin studies indicating that the heritability of life span considered as a quantitative trait is between 20% and 30% (28)(29)(30). The results of these studies in which few subjects survived beyond age 85 should not be interpreted as an indication of the genetic contribution to achieving much older age, that is, the nonagenarian years and beyond.…”
Section: Discussionmentioning
confidence: 63%
“…It is worth noting that the above evidence for a substantial and significant genetic effect on the likelihood of reaching exceptionally old age is not inconsistent with several twin studies indicating that the heritability of life span considered as a quantitative trait is between 20% and 30% (28)(29)(30). The results of these studies in which few subjects survived beyond age 85 should not be interpreted as an indication of the genetic contribution to achieving much older age, that is, the nonagenarian years and beyond.…”
Section: Discussionmentioning
confidence: 63%
“…Many biogerontologists have argued that human life-expectancy is largely due to genetics [1,2]. However, it has been well-documented that only 20%-30% of human life-expectancy is explained by genetic variation [2][3][4]. Some researchers have concluded that psychosocial resources play an essential role in explaining aging processes beyond biology; Poon et al, and Silverstein et al [5,6] noted that psychosocial theories of aging serve as useful tools to examine unexplained complexities in human aging.…”
Section: Evidence Of Psychosocial Theories Among the Oldest-oldmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Although these studies do not distinguish between shared environmental and genetic factors, twin data suggest that genes may have a modest role in achieving longevity. 12,13 In order to better distinguish the effect of genes from the effect of shared familial environment, Schoenmaker et al 3 analyzed the survival data of the spouses of long-lived subjects as an additional control group. They found that members of this control group, who shared most of their adult life with the long-lived partner, did not show any advantage/benefit in terms of survival, suggesting that a substantial contribution in the familiarity of human longevity is attributable to genetic factors.…”
Section: Introductionmentioning
confidence: 99%